2012
DOI: 10.5539/ass.v8n12p21
|View full text |Cite
|
Sign up to set email alerts
|

Can Literature Improve English Proficiency: The Students Perspective

Abstract: Promoting the interest of learning English Language through the teaching of literature is considered to improve the proficiency of the students in the target language too. Therefore, this study aims to investigate whether the teaching of literature promotes students' proficiency in the target language. Thus this study has taken into account the students' feedback on the subject, teaching methodologies employed by teachers and the literary texts used in the school. The survey was conducted at SMK Bukit Besi to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 3 publications
(2 reference statements)
0
11
0
3
Order By: Relevance
“…A number of studies were conducted to investigate the literature teaching approaches in ESL classroom (Bridget & Omar, 2007;Tina et al, 2007;Ghazali et al, 2009;Divsar & Tahriri, 2009;Rashid et al, 2010;Mustakim et al, 2014). Most of these studies demonstrated an increasing awareness of the importance of using appropriate approaches to the teaching of English literature (Amer, 2003;Khatib et al, 2011a).…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of studies were conducted to investigate the literature teaching approaches in ESL classroom (Bridget & Omar, 2007;Tina et al, 2007;Ghazali et al, 2009;Divsar & Tahriri, 2009;Rashid et al, 2010;Mustakim et al, 2014). Most of these studies demonstrated an increasing awareness of the importance of using appropriate approaches to the teaching of English literature (Amer, 2003;Khatib et al, 2011a).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study found that the information-based approach and paraphrastic approach were the most favored approaches by teachers in the teaching of CCL programs. Ghazali et al (2009) also explored the teaching strategies and the students' attitudes towards the literature texts used in Malaysian secondary schools. The study found that students have positive attitudes towards the text selection although they were less enthusiastic about the teaching methods used by teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations